Simulation of bulk phases formed by polyphilic liquid crystal dendrimers - Ilnytskyi, J.M.; Lintuvuori, J.S.; Wilson, M.R. (Condensed Matter Physics, 2010)
A coarse-grained simulation model for a third generation liquid crystalline dendrimer (LCDr) is presented. It allows, for the rst time, for a successful molecular simulation study of a relation between the shape of a polyphilic macromolecular mesogen and the symmetry of a macroscopic phase. The model dendrimer consists of a soft central sphere and 32 grafted chains each terminated by a mesogen group. The mesogenic pair interactions are modelled by the recently proposed soft core spherocylinder model of Lintuvuori and Wilson [J. Chem. Phys, 128, 044906, (2008)]. Coarse-grained (CG) molecular dynamics (MD) simulations are performed on a melt of 100 molecules in the anisotropic-isobaric ensemble. The model LCDr shows conformational bistability, with both rod-like and disc-like conformations stable at lower temperatures. Each conformation can be induced by an external aligning eld of appropriate symmetry that acts on the mesogens (uniaxial for rod-like and planar for disc-like), leading to formation of a monodomain smectic A (SmA) or a columnar (Col) phase, respectively. Both phases are stable for approximately the same temperature range and both exhibit a sharp transition to an isotropic cubic-like phase upon heating. We observe a very strong coupling between the conformation of the LCDr and the symmetry of a bulk phase, as suggested previously by theory. The study reveals rich potential in terms of the application of this form of CG modelling to the study of molecular self-assembly of liquid crystalline macromolecules. Розроблено огрублену модель рідкокристалічного дендримера (РКД) 3-ї генерації, завдяки чому вперше в літературі вивчено взаємозв'язок між формою рідкокристалічної макромолекули та симетрією макроскопічної фази за допомогою молекулярної динаміки. Модель складається з м'якої центральної сфери, до якої приєднано 32 ланцюжки, кожен із яких закінчується мезогенною групою. Останні взаємодіють за допомогою недавно запропонованого анізотропного потенціалу з м'якою серцевиною Лінтувуорі та Вілсона [J. Chem. Phys, 128, 044906, (2008)]. За допомогою методу огрубленої молекулярної динаміки змодельовано розплав 100 молекул РКД в анізотропно-ізобаричному ансамблі. Запропонована модель РКД продемонструвала конформаційну бістабільність, за якої як паличкоподібна, так і дископодібна конформації виявляються стабільними за низьких температур. Кожна з цих 2-х конформацій може ініціюватись зовнішнім полем із відповідною симетрією, в результаті в розплаві спонтанно формуються або монодоменна смектична фаза (із паличкоподібних конформацій, ініційованих одновісним полем), або стовпцева фаза (із дископодібних конформацій, ініційованих планарним полем). Обидві фази є стабільними приблизно в тому ж температурному інтервалі та у процесі нагрівання переходять в ізотропну кубічну фазу через яскраво виражений фазовий перехід. Спостережено сильний зв'язок між конформацією РКД і симетрією об'ємної фази, на що вказано раніше в теоретичних роботах. Дослідження виявляє великий потенціал в застосуванні огрубленого моделювання до опису просторової самоорганізації рідкокристалічних макромолекул.